`You can change your life through sports' physical activity interventions to improve the health and well-being of adults experiencing homelessness: a mixed-methods systematic review - Broderick, Julie (My University, 2024)
Objectives: Systematically synthesise evidence of physical activity interventions for people experiencing homelessness (PEH). Design: Mixed-methods systematic review. Data sources: EMBASE, Web of Science, CINAHL, PubMed (MEDLINE), PsycINFO, SPORTDiscus and Cochrane Library, searched from inception to October 2022. Eligibility criteria: PICO framework: population (quantitative/qualitative studies of PEH from high-income countries); intervention (physical activity); comparison (with/without comparator) and outcome (any health/well-being-related outcome). The risk of bias was assessed using Joanna Briggs Institute critical appraisal tools. Results: 3615 records were screened, generating 18 reports (17 studies, 11 qualitative and 6 quantitative (1 randomised controlled trial, 4 quasi-experimental, 1 analytical cross-sectional)) from the UK, USA, Denmark and Australia, including 554 participants (516 PEH, 38 staff). Interventions included soccer (n=7), group exercise (indoor (n=3), outdoor (n=5)) and individual activities (n=2). The risk of bias assessment found study quality to vary; with 6 being high, 6 moderate, 4 low and 1 very low. A mixed-methods synthesis identified physical and mental health benefits. Qualitative evidence highlighted benefits carried into wider life, the challenges of participating and the positive impact of physical activity on addiction. Qualitative and quantitative evidence was aligned demonstrating the mental health benefits of outdoor exercise and increased physical activity from indoor group exercise. Quantitative evidence also suggests improved musculoskeletal health, cardiovascular fitness, postural balance and blood lipid markers (p<0.05). Conclusion: Qualitative evidence suggests that physical activity interventions for PEH can benefit health and well-being with positive translation to wider life. There was limited positive quantitative evidence, although most was inconclusive. Although the evidence suggests a potential recommendation for physical activity interventions for PEH, results may not be transferable outside high-income countries. Further research is required to determine the effectiveness and optimal programme design.
PUBLISHED
Keywords: Exercise; Health; Physical activity; Physical fitness; Public health; Inclusive Society